2020
DOI: 10.20884/1.jks.2020.15.2.1160
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Knowledge and Confidence of Mothers in Caring for Low Birth Weight Babies Through Education from the Maternal and Child Health Handbook

Abstract: <p>Having a Low Birth Weight (LBW) is one of the risk factors that may lead to stunting in children under five years old. An education program based on the Maternal and Child Health handbook (MCH) for the first 1000 days of a child’s life is one way to prevent the impact of stunting by improving the mothers’ knowledge and self-confidence to look after LBWB. The study is designed along the line of pre-post quasi-experimental research with a control group, involving 69 samples of mothers with LBWB that mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
4
0
3
Order By: Relevance
“…Research by Premji et al (2016) et al reported that mothers with LBW babies had low parenting confidence until 6~8 weeks after delivery which is similar to another study that stated in the initial period that postpartum mothers had low self-efficacy (Sugiarti, Rustina, and Efendi 2020;Vance et al 2021). They also faced obstacles in carrying out their roles, both internal and external, including insufficient knowledge, stress, economic problems, and family and social support (Astuti et al 2019).…”
Section: Introductionmentioning
confidence: 64%
“…Research by Premji et al (2016) et al reported that mothers with LBW babies had low parenting confidence until 6~8 weeks after delivery which is similar to another study that stated in the initial period that postpartum mothers had low self-efficacy (Sugiarti, Rustina, and Efendi 2020;Vance et al 2021). They also faced obstacles in carrying out their roles, both internal and external, including insufficient knowledge, stress, economic problems, and family and social support (Astuti et al 2019).…”
Section: Introductionmentioning
confidence: 64%
“…Providing information as an effort to increase knowledge can be conducted individually or in groups through group discussions (13). The media used in health education might also vary such as leaflets, books, websites or applications (14,15). The information media at this time gives mothers easy access to all information needs, with the availability to the information which is informative and reliable and also facilitate mothers to ask questions and discuss with health workers or friends (16) In order to reduce neonatal morbidity and mortality due to premature birth, there is an important need to increase the knowledge and skills not only for mothers but also other caregivers at home such as grandmothers.…”
Section: Health Educationmentioning
confidence: 99%
“…Teknologi M-Health pada kesehatan anak juga sudah tidak asing lagi. Hasil penelitian membuktikan bahwa teknologi sudah banyak digunakan oleh orangtua maupun tenaga kesehatan, antara lain untuk pemantauan kesehatan anak, pemantauan tumbuh kembang pada anak, meningkatkan pengetahuan dan keterampilan ibu dalam pemantauan tumbuh kembang anak, meningkatkan interaksi anatara ibu dan bidan, meningkatkan peran kader posyandu, meningkatkan pengetahuan dan kepercayaan diri ibu dalam merawat BBLR serta sebagai alat deteksi dini status gizi balita (Amaliah et al, 2018;Muliyana, 2020;Rinawan et al, 2019;Sugiarti et al, 2020;. Hal ini menunjukkan bahwa M-Health dapat menjadi teknologi yang efektif untuk membantu dalam pemantauan kesehatan, pertumbuhan dan perkembangan anak, memberikan dampak positif untuk orangtua maupun tenaga kesehatan (Lulianthy et al, 2020b(Lulianthy et al, , 2020a.…”
Section: Metode Penelitianunclassified